Legal and procedural constraints in the execution of wasiyyah (Islamic will) in Malaysia - Wasri Ahmad Sujani (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2014)
Islamic law on wasiyyah (will) imposes two principal constraints upon testamentary power namely, the testator is constrained to bequeath in favor of legal heirs and the disposition may not exceed one-third of his net estate. However, the majority of jurists (Jumhur) opine that such a disposition is valid if unanimously agreed by the legal heirs. Although consent, as justified by Muslim jurists, plays a critical role to invalidate such limitations, there exists a great need to clarify its pre-conditions in evading this reservation from being vitiated and abused. Accordingly, the research is undertaken based on the premise that a wasiyyah which goes against the legal constraints or ultra vires wasiyyah, is not absolutely void, but is voidable or ab initio valid, and conditional upon the required consent. For this purpose, the research adopts a quantitative and comparative analysis in dealing with the number of ahadith reported in Sunan al-Sittah. The use of textual analysis as a method in tabling ahadith enables this research to elicit the legitimacy of legal constraints on wasiyyah. This research endeavors to lay down the miscellaneous views of ancient and contemporary Muslim jurists in their literatures pertaining to the position of these legal constraints. In this respect, reported cases are discussed to look into the practical application of the testacy law in Malaysia thus far. The research also consists of an analysis of the law as provided by the applicable statutes that operate as general application to specify the jurisdiction of the several administrative bodies and their scopes. This is an attempt to highlight some of what is seen as obstacles presented by the procedural framework in Malaysia. The research infers that ultra vires wasiyyah is justifiably relevant subject always to the consent of the legal heirs. This can facilitate a comprehensive description on what is exactly the Islamic stance on a bequest to heirs and its allowable portion. The research also reveals the paramount importance of having a codified Islamic law towards achieving uniformity in the law relating to the execution of wasiyyah in Malaysia.